Pendidikan karakter dalam revolusi 4.0: Membangun etika digital dan kemampuan berpikir kritis - Hidayah, Shilfina (Maliki Interdisciplinary Journal, 2024)
The development of digital era is still ongoing. Many technologies continue to develop in a better direction. This has an impact in all areas. Current business changes require every business actor to change the way they run their business by utilizing digital platforms. Technological changes which are becoming more sophisticated day by day have an impact on social interaction which causes an imbalance between old norms and the current situation so that social control is needed from those closest to them and their external environment